2017
DOI: 10.1161/atvbaha.116.308401
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of RNA Polymerase I With the Small-Molecule CX-5461 for Prevention of Arterial Injury–Induced Neointimal Hyperplasia

Abstract: Objective-RNA polymerase I (Pol I)-dependent rRNA synthesis is a determinant factor in ribosome biogenesis and thus cell proliferation. The importance of dysregulated Pol I activity in cardiovascular disease, however, has not been recognized. Here, we tested the hypothesis that specific inhibition of Pol I might prevent arterial injury-induced neointimal hyperplasia. Approach and Results-CX-5461 is a novel selective Pol I inhibitor. Using this tool, we demonstrated that local inhibition of Pol I blocked balloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 54 publications
6
24
2
Order By: Relevance
“…cx-5461 accelerated the occurrence of AD, inhibited the proliferation of ASMCs, and induced apoptosis. In a recent study, Ye et al reported that cx-5461 prevented aortic intima hyperplasia, indicating its clinical potential against atherosclerosis and stenosis [44]. In contrast to our study, however, they showed that cx-5461 only inhibited ASMC proliferation and did not induce apoptosis [43].…”
Section: Discussioncontrasting
confidence: 96%
“…cx-5461 accelerated the occurrence of AD, inhibited the proliferation of ASMCs, and induced apoptosis. In a recent study, Ye et al reported that cx-5461 prevented aortic intima hyperplasia, indicating its clinical potential against atherosclerosis and stenosis [44]. In contrast to our study, however, they showed that cx-5461 only inhibited ASMC proliferation and did not induce apoptosis [43].…”
Section: Discussioncontrasting
confidence: 96%
“…protein (Boulon et al, 2010). Similar to our findings in aortic smooth muscles (Ye et al, 2017), however, CX-5461 did not increase the total amount of p53 protein; instead it induced a robust increase in p53 phosphorylation (Figure 5d,e). Moreover, pretreatment with the selective p53 inhibitor pifithrin-α attenuated the inhibitory effect of CX-5461 on the cell cycle (see Figure 5b).…”
Section: Cx-5461 Attenuates Inflammatory Cell Infiltration In Pah Lsupporting
confidence: 90%
“…In addition to the activation of the p53 pathway, NSR may also signal to other pathways implicated in regulating cell cycle and apoptosis (James et al, ). Interestingly, we and other groups have observed in different cells that induction of NSR by selective inhibition of RNA polymerase I triggers activation of the ATR pathway, possibly independent of DNA strand breaks (Ma & Pederson, ; Quin et al, ; Ye et al, ). Hence, it is plausible that the nucleolus serves as a signaling hub, while Sirt1 may intervene with multiple pathways by regulating the occurrence of NSR.…”
Section: Discussionmentioning
confidence: 76%
“…Treatment with resveratrol attenuated NSR induced by H 2 O 2 , while this effect of resveratrol was blunted by EX‐527 (Figure e). We and others have shown that NSR induction by inhibiting RNA polymerase I triggers cell cycle arrest (Negi & Brown, ; Ye et al, ). To test whether Sirt1 could also inhibit NSR‐associated cellular functional changes, we performed flow cytometry analysis; we showed that ActD treatment caused G2/M blockade, which was attenuated by Sirt1 overexpression (Figure f).…”
Section: Resultsmentioning
confidence: 87%